A low-overhead PUF for anti-clone attack of RFID tags. (August 2022) - Shuyu, Chen; Limin, Yan
Abstract: Physically Unclonable Function (PUF) is one of the important research techniques for anti-cloning attacks in Radio Frequency Identification (RFID) tags security. But in RFID tags, there are not quite a few resources left for PUF. Therefore, this paper designs a new lightweight reconfigurable XOR RO PUF, which can simultaneously switch the internal delay of each inverter and the number of ring oscillator stages, increase the delay complexity with less hardware overhead, and generate more multiple authentication keys. In this paper, the proposed PUF circuit design is verified and good performance indicators are obtained. By comparison with the existing PUF low-overhead design, this design has more challenge/response pairs (CRPs) and less hardware overhead without reducing the uniformity, randomness, uniqueness and reliability of the PUF.